On the spectral difference between electroluminescence and photoluminescence of Si nanocrystals: a mechanism study of electroluminescence - Wang, Dong-Chen; Chen, Jia-Rong; Zhu, Jiang; Lu, Chen-Tian; Lu, Ming (Journal of nanoparticle research : an interdisciplinary forum for nanoscale science and technology, 2013)
Spectral shift, especially blueshift, in peak position of electroluminescence (EL) spectrum of Si nanocrystal (Si-nc) with respect to its photoluminescence (PL) counterpart has been often observed. Explanations for the spectral difference are different for different EL mechanisms adopted. To gain a relevant picture of the EL process, in this work, we analyze three EL mechanisms that are mainly applied nowadays, i.e., the model of defect light emission, that of band-filling, and that of Si-nc size selection by the carrier energy. Different Si-nc samples and working conditions are designed and their EL and PL emissions monitored according to the predictions of the three models. It is concluded that the observed EL is mainly of Si-nc-related origin. The experimental results are more consistent with the model of Si-nc size selection.